Mewujudkan Pendidikan Untuk Semua: Studi Implementasi Pendidikan Inklusif di Indonesia - Justin Niaga Siman Juntak; Alfredo Rynaldi; Eka Sukmawati; Mudrikatul Arafah; Tekat Sukomardojo (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2023)
Inclusive education is an educational model that emphasizes equality, participation, and respect for diversity in the educational environment. This research will analyze policies, challenges, the role of the teacher, positive impacts, best practice models, as well as evaluating and improving the implementation of inclusive education in Indonesia. This research is based on a descriptive qualitative approach and data is collected through literature studies on previous studies and studies. The results show that despite challenges and obstacles, inclusive education has a positive impact on participation, social-emotional development, and respect for diversity. Collaborative efforts are needed between the government, educational institutions, teachers and the community to improve the implementation of inclusive education in Indonesia and ensure equal access to education for all students